Meningkatkan Hasil Belajar Siswa dengan Metode Problem Based Learning Materi Manusia Citra Allah Fase D Kelas VII SMP Xaverius 3 Bandar Lampung - Eknasius Nung Anung Wibowo (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to improve students' understanding and improve student learning outcomes in the subject of Catholic Religion for grade 7 of SMP Xaverius 3 Bandar Lampung in the 2024-2025 academic year through the application of the PBL method at SMP Xaverius 3 Bandar Lampung. This method was chosen because it can stimulate critical thinking, creativity, and students' problem-solving abilities. This type of research is classroom action research (CAR). This study uses quantitative and qualitative approaches with a classroom action research design. The subjects of the study were grade 7 students at SMP Xaverius 3 Bandar Lampung. The research instruments used involved comprehension tests, observations, interviews, and documentation. The first cycle discussed I was created as a unique person, and the second cycle discussed I am Proud as a Woman and a Man. The application of the PBL method was carried out in several stages, including problem identification, information collection, analysis, solution formulation, and evaluation. The results of the study showed a significant increase in students' understanding of Catholic Religion topics. Thus, this study makes a positive contribution to efforts to improve the quality of Catholic religious learning at SMP Xaverius 3 Bandar Lampung through the application of the PBL method. The implication of this study is that this method can be adopted in similar learning contexts to improve students' understanding of materials, especially Catholic religious education.